The effect of jet deflection on the interference of a rearward facing jet - Craven, A. H. (College of Aeronautics, 1957)
This paper contains the results of an experimental investigation into the effects induced by a deflected jet upon the body from which it issues. The tests were performed at a Reynolds number of 0.3 x 10(6) based on body diameter and maximum tunnel velocity. It was found that a side force and moment were induced upon the afterbody, the magnitude of which increased with jet deflection and jet thrust. The direction of the induced side force was in a direction opposite to the normal component of the thrust vector. The base drag increased with jet thrust but decreased with increase of jet deflection for small deflections.